Divided loyalties: young Somali Americans and the lure of extremism - Weber, Joseph (Michigan State University Press, 2020)
Introduction -- The Seeds of Jihad -- A Land of Chaos -- The First Wave -- Blind Devotion -- A Cautionary Tale -- Don't Let the Caravan Leave You -- Why ISIS? -- A Special Case -- Peer to Peer -- A Woman's Place? -- Brotherhood -- The Caravan Beckons Again -- The Glory of the Shahid -- Breaking Down -- A Very Real Threat -- Straight Out of Hollywood -- The Backlash -- The Judge -- A Closed World? -- Taking a Hard Look -- Moving